New species and records of Maechidius Macleay, 1819 from New Guinea (Coleoptera: Scarabaeidae: Melolonthinae) - Prokofiev, Artem M. (Zootaxa, 2022)
Seven species of Maechidius Macleay, 1819 from New Guinea are described, namely M. addarcis Prokofiev, new species, M. astrolabius Prokofiev, new species, M. bombycinus Prokofiev, new species, M. echinoides Prokofiev, new species, M. macrosoma Prokofiev, new species, M. penicilliger Prokofiev, new species, and M. telnovi Prokofiev, new species. Males of M. interruptocarinulatus Heller, 1914 and aedeagus of M. seriepunctatus Moser, 1920 are described for the first time. Key to the Indonesian and New Guinean species is amended for inclusion of the newly described species.